Explaining the Multifaceted Patterns of Migrant Entrepreneurship in the Global Economy: A Resource-Based Approach - Alessandro Arrighetti; Jacopo Canello (ZBW – Leibniz Information Centre for Economics, 2023)
This article aims to propose a novel theoretical framework to interpret the recent patterns of migrant entrepreneurship in the global economy. Our theoretical framework builds on the resource-based view and highlights the role of the migrant enterprise as a collective entity endowed with peculiar tangible and intangible resources. The specific endowment of each migrant firm determines its competitive advantages and disadvantages, as well as its ability to acquire and process knowledge over time and internationalize. Such an approach allows to categorize the migrant enterprise as an autonomous entity, providing a reliable explanation of the heterogeneous features and performances displayed by these firms in the global economy. Indeed, even when migrant firms operate in the same host environment and are managed by entrepreneurs of the same ethnic background, their performances tend to be significantly different. Using a resource-based approach, the peculiar features of the migrant enterprise can be disentangled and explained more effectively.
Keywords: 330; Migrant entrepreneurship; Resorce-based View; Heterogeneity; Host Environment